2003
DOI: 10.1074/jbc.m304400200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Plasma Membrane Na+/H+ Exchanger NHE1 by Sustained Intracellular Acidosis

Abstract: Activity of the Na؉ /H ؉ exchanger (NHE) isoform 1 (NHE1) is increased by intracellular acidosis through the interaction of intracellular H ؉ with an allosteric modifier site in the transport domain. Additional regulation is achieved via kinase-mediated modulation of the NHE1 regulatory domain. To determine if intracellular acidosis stimulates NHE1 activity solely by the allosteric mechanism, we subjected cultured neonatal rat ventricular myocytes (NRVM) with native NHE1 expression to intracellular acidosis (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 42 publications
5
105
1
18
Order By: Relevance
“…We found that this method of stimulation of these cells resulted in increased activity and phosphorylation of the protein that could be blocked by MEK inhibition. Our results on stimulation of activity of NHE1 were similar to those of Haworth et al (17). It should be noted that our results differ from those Hayashi et al (22), who did not find that sustained intracellular acidosis stimulates NHE1 activity.…”
Section: /Hsupporting
confidence: 51%
See 2 more Smart Citations
“…We found that this method of stimulation of these cells resulted in increased activity and phosphorylation of the protein that could be blocked by MEK inhibition. Our results on stimulation of activity of NHE1 were similar to those of Haworth et al (17). It should be noted that our results differ from those Hayashi et al (22), who did not find that sustained intracellular acidosis stimulates NHE1 activity.…”
Section: /Hsupporting
confidence: 51%
“…We examined ERK-dependent phosphorylation because in several earlier studies we have shown both ERK-dependent phosphorylation of the NHE1 protein and ERKdependent stimulation of activity (10,11). Sustained intracellular acidosis was earlier shown to be a reliable method of stimulation of Na ϩ /H ϩ exchanger activity by ERK-dependent pathways (17). In preliminary experiments we found that it was a more reliable method of activation of NHE1 in this cell type in comparison with receptor-mediated activation.…”
Section: /Hmentioning
confidence: 91%
See 1 more Smart Citation
“…This activates the plasmalemmal Na + /Ca ++ exchanger inducing a deleterious increase of intracellular Ca ++ that triggers various pathways ultimately leading to cell death [74,99,98,77]. Genetic ablation or pharmalogic inhibition of NHE1 during episodes of ischemiareperfusion mitigated cardiac and neural injuries both in vivo and in vitro in rodents and pigs [85,32,62]. Consistent with this, NHE1 overactivity has been linked to cardiac hypertrophy and heart failure [168].…”
Section: Slc9a1-nhe1mentioning
confidence: 76%
“…Prolonged Acidosis Is Not Responsible for NHE1 Activation following OGD/REOX-It has been reported that prolonged acidosis (pH i of 6.55) for 3 min in rat ventricular cardiomyocytes leads to ERK1/2-dependent stimulation of NHE1 activity (26). 2 h OGD reduced basal pH i from 7.09 to 6.80 in astrocytes (6).…”
Section: Nhe1 Kinase P90 Rsk Is Downstream Effector Of Erk1/2-p90mentioning
confidence: 99%